2005
DOI: 10.1021/jf050499m
|View full text |Cite
|
Sign up to set email alerts
|

Organoarsenical Species Contents in Cooked Seafood

Abstract: The organoarsenical species arsenobetaine (AB), arsenocholine (AC), tetramethylarsonium ion (TMA+), dimethylarsinic acid (DMA), and monomethylarsonic acid (MMA) were determined in 64 cooked seafood products (fish, bivalves, squid, crustaceans) included in a Total Diet Study carried out in the Basque Country (Spain). For cooking, various treatments were employed (grilling, roasting, baking, stewing, boiling, steaming, microwaving). The results obtained show that in cooked seafood AB is the major species, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 26 publications
0
21
0
3
Order By: Relevance
“…[154][155][156][157] However, we found that cooking in water (stewing, boiling or steaming) did not decrease the content of AB [154]. One previous study has also indicated that AB can be degraded in an oxidative environment [158].…”
Section: Effect Of Storage and Processing On Concentration And Stabilmentioning
confidence: 60%
See 1 more Smart Citation
“…[154][155][156][157] However, we found that cooking in water (stewing, boiling or steaming) did not decrease the content of AB [154]. One previous study has also indicated that AB can be degraded in an oxidative environment [158].…”
Section: Effect Of Storage and Processing On Concentration And Stabilmentioning
confidence: 60%
“…Generally, the pattern of arsenicals does not seem to be altered much due to processing, however, most seafood processing studies have found an increase in TETRA after heat application [154][155][156][157]. Since TETRA is considered to be more toxic than AB, the increase in TETRA in seafood processed at high temperatures should be taken into account when assessing the safety of such products [128].…”
Section: Discussionmentioning
confidence: 99%
“…Freezing and storage were observed to cause decreases in AB and total As in mussels but not finfish (Dahl et al 2010). Loss of water during cooking can lead to an increase in concentration in total As or iAs in some seafood types (Devesa et al 2005), whereas a loss of soluble As from seaweed has also been observed (Devesa et al 2008). Heating has been associated with the transformation of AB to TETRA (Devesa et al 2001, Dahl et al 2010), but there is little information on transformation of other organic As species.…”
Section: Sources and Distribution Of Organic As Species In Marine mentioning
confidence: 99%
“…The study indicated that the decreases depended upon cooking conditions, such as time, temperature and cooking medium. Devesa et al (2005) determined several organic arsenic species in 64 cooked seafood products and compared the results with the raw products. The results showed that in cooked seafood arsenobetaine is the major arsenic species followed by dimethylarsinate and tetramethylarsonium ion.…”
Section: Food Preparationmentioning
confidence: 99%